The Phenomenology Of Nothingness - Hussey, James Leo (My University, 1992)
This thesis attempts to render a comprehensive interpretation of Heidegger's concept of nothingness as it is argued for in Being and Time. This thesis has two main objectives: 1) to reinterpret Heidegger's concept of the anxiety in which Dasein experiences nothingness and to argue against the standard interpretation which states that Dasein experiences anxiety or nothingness when it acknowledges its mortality, and 2) to show that section 40 of Being and Time should be interpreted independently from later sections. The main emphasis of this thesis is to clarify what Heidegger means by nothingness and to criticize those who misinterpret Heidegger. I attempt to provide a more satisfactory account of nothingness and its relation to anxiety and death.
In chapter I, merely give an account of Heidegger's concept of inauthenticity, which includes the following concepts: The "they", averageness, distantiality, levelling down, publicness, idle talk, curiosity, ambiguity, and falling and throwness.
In chapter II, I discuss anxiety and nothingness. refer to Heidegger's essay entitled "What is Metaphysics?" in order to get a deeper understanding of Heidegger's concept of nothingness. I argue against the standard interpretation and show that nothingness can be experienced without the acknowledgement of one's mortality.
In chapter III, I attempt to answer the following question: What does Heidegger mean by death? I outline the arguments of various interpreters of Heidegger's concept of death. They equate nothingness with one's acknowledgement of mortality, i.e., the possibility of one's own death. Those who argue for this position do not understand what Heidegger means by nothingness and its significance to death. I criticize these interpreters and reveal their oversights and misinterpretations, and then put forth my own interpretation of what Heidegger means by death.
Keywords: Heidegger; concept of nothingness; Being and Time; Philosophy; Philosophy